Nurses' 'worry' as predictor of deteriorating surgical ward patients: A prospective cohort study of the Dutch-Early-Nurse-Worry-Indicator-Score. (July 2016) - Douw, Gooske; Huisman-de Waal, Getty; van Zanten, Arthur R.H.; van der Hoeven, Johannes G.; Schoonhoven, Lisette
Abstract: Background: Nurses' 'worry' is used as a calling criterion in many Rapid Response Systems, however it is valued inconsistently. Furthermore, barriers to call the Rapid Response Team can cause delay in escalating care. The literature identifies nine indicators which trigger nurses to worry about a patient's condition. Objectives: The objective of this study is to determine the significance of nurses' 'worry' and/or indicators underlying 'worry' to predict unplanned Intensive-Care/High-Dependency-Unit admission or unexpected mortality among surgical ward patients. Design: A prospective cohort study. Settings: A 500-bed tertiary University affiliated teaching hospital. Participants: Adult, native speaking surgical patients, admitted to three surgical wards (traumatology, vascular- and abdominal/oncological surgery). We excluded patients with a non-ICU policy or with no curative treatment. Mentally incapacitated patients were also excluded. Methods: We developed a new clinical assessment tool, the Dutch-Early-Nurse-Worry-Indicator-Score (DENWIS) based on signs underlying 'worry'. Nurses systematically scored their 'worry' and the DENWIS once per shift or at any moment of 'worry'. DENWIS measurements were linked to routinely measured vital signs. The composite endpoint was unplanned Intensive-Care/High-Dependency-Unit admission or unexpected mortality. The DENWIS-indicators were included in a univariate and multivariate logistic regression analysis, subsequently inserting 'worry' and the Early Warning Score into the model. We calculated the area under the receiver-operating characteristics curve. Results: In 3522 patients there were 102 (2.9%) patients with unplanned Intensive Care Unit/High Dependency Unit-admissions or unexpected mortality. 'Worry' (0.81) and the DENWIS-model (0.85) had a lower area under the receiver-operating characteristics curve than the Early Warning Score (0.86). Adding 'worry' and the Early Warning Score to the DENWIS-model resulted in higher areas under the receiver operating characteristics curves (0.87 and 0.91, respectively) compared with the Early Warning Score only based on vital signs. Conclusions: In this single-center study we showed that adding the Early Warning Score based on vital signs to the DENWIS-indicators improves prediction of unplanned Intensive-Care/High-Dependency-Unit admission or unexpected mortality.